Uso de las tecnologías de la información y la comunicación en la comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria en instituciones educativas públicas del distrito de San Juan Bautista 2022 - Caro Tuesta, Teddy Isaias (2024)
The present research aims to explain the influence of the use of ICTs on third-grade high school students’ reading comprehension skills in English at San Juan Bautista district public schools in 2022. An explanatory research design was employed, which included contemporary cross-sectional and multivariable field designs. The total population consisted of 1957 students, and a sample of 321 students was selected using stratified probability sampling with proportional allocation. The reference population was 15 English teachers. Data collection was carried out through a reading comprehension test and a valid and reliable questionnaire. The results indicate that the correlation (Rho) between the use of ICTs and the reading comprehension texts was 0.267 (teachers 0.394), which was higher than α = 0.05. For information and literacy, it was 0.244 (teachers 0.794), for communication and collaboration, it was 0.321 (teachers 0.923), for digital content creation, it was 0.093 (teachers 0,708), for digital security, it was 0.349 (teachers 0.282), and for problem solving, it was 0.186 (teachers 0.326). Statistical analysis showed a p-value greater than the significance level of α = 0.05. Therefore, it is concluded that, due to the lack of a significant correlation, there is no influence of the use of ICTs and any variable on the study population’s reading skills in English.